Communication Strategies Used by the Primary Teachers in EFL Classroom - Ayu Oktaviani; Dwi Misgiyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of the research was to find out communication strategies used by the Primary teachers in EFL classroom. The sample of the research was 3 teachers in grade 2, 5 and 6 at Palm Kids Elementary School of Lubuklinggau. The samples were taken through Purposive sampling. The researcher used descriptive qualitative research and the data were collected by using observation, interview, and documentation(field note and video recording). The result revealed that communiction strategies used by the English teachers’ were code switching, intra-lingual, IL based strategies, non-linguistics, cooperative, and formal reduction. In the other English teachers’ responded towards are the communication strategies helped the students understood the meaning, made the students easier to understood the material, helped students to understand what English said, helped to explain the material more detail in teaching and learning process and made the students have to master English well. Keyword: primary teachers, communication strategies, primary school